On **b-t**-sets and **b-**t-sets in Topological Spaces - A. Devika; P. Perianayaki (International Journal of Mathematics And its Applications, 2016)
The aim of this paper is to introduce the new concepts of **t-sets and t**-sets, **b-t**- sets,**b-**t-sets in the topological space and discuss some properties and characterization of these new notions.